2015
DOI: 10.1016/j.bpg.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's oesophagus: Frequency and prediction of dysplasia and cancer

Abstract: The incidence of esophageal adenocarcinoma is continuing to increase at an alarming rate in the Western world today. Barrett’s esophagus is a clearly recognized risk factor for the development of esophageal adenocarcinoma, but the overwhelming majority of patients with Barrett’s esophagus will never develop esophageal cancer. A number of endoscopic, histologic and epidemiologic risk factors identify Barrett’s esophagus patients at increased risk for progression to high-grade dysplasia and esophageal adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…However, the natural history of BE is incompletely understood. Overall, the incidence of progression from metaplasia to high-grade dysplasia (HGD) or EAC is approximately 0.26–0.63 % per year [ 6 ], and that to EAC alone 0.12 % [ 7 ]. However, only a minority of patients progress to low-grade dysplasia (LGD), and of those that do similarly only a minority ultimately progress to HGD or EAC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the natural history of BE is incompletely understood. Overall, the incidence of progression from metaplasia to high-grade dysplasia (HGD) or EAC is approximately 0.26–0.63 % per year [ 6 ], and that to EAC alone 0.12 % [ 7 ]. However, only a minority of patients progress to low-grade dysplasia (LGD), and of those that do similarly only a minority ultimately progress to HGD or EAC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of EAC is increasing and due to late carcinoma detection the 5-year survival rate is low (less than 20 %) (17,18). As well as BE as a complication of gastroesophageal reflux disease, there are other well known risk factors for EAC such as male gender, smoking and obesity (19)(20)(21).…”
Section: A B Cmentioning
confidence: 99%
“…The length of BE segment is also assessed as a risk factor for EAC progression. The risk of progression increased from 19 % to 28 % for every 1 cm increase in the length of the BE (19,24,25). Richardson et al (26) in 2018 in his work showed that multiple real -time pCLE can evaluate the entire segment of the BE.…”
Section: A B Cmentioning
confidence: 99%
“…Obesity, in particular a body mass index of >30 is associated with an approximate 2-fold increased risk for EAC (17). Strong epidemiologic risk factors include aging, male gender, obesity and smoking (18). The regional differences observed in the incidence of EAC indicate that race is a strong risk factor for EAC.…”
Section: Epidemiologymentioning
confidence: 99%
“…The maximum stand uptake value (SUVmax) together with the tumor/normal esophageal ratio could be used to evaluate the effect of neoadjuvant chemotherapy (82). Additionally, [(18)F] fluorodeoxyglucose (FDG)-PET positive lymph node analysis can be used to predict survival of patients who underwent neoadjuvant chemotherapy (83). Additional factors predicting outcome of neoadjuvant therapy can be found in a recent review by Tao et al (84).…”
Section: Treatmentmentioning
confidence: 99%